Morphologic expression of the left coronary artery in pigs. An approach in relation to human heart - Gómez,Fabian Alejandro (2014)
Introduction: In spite of its importance as an experimental model, the information on the left coronary artery in pigs is sparse. Objective: To determine the morphologic features of the left coronary artery in pigs. Methods: We evaluated 158 pig hearts. The left coronary artery was perfused with synthetic resin after their ostia had been catheterized. Diameters and courses of the vascular beds were measured with an electronic caliper (Mitutoyo(r)). Results: The diameter of left coronary artery was 6.98 ± 1.56 mm and its length was 3.51±0.99 mm. It was found to end up by bifurcating itself into the anterior interventricular artery and the circumflex artery in 79% of the cases, and by trifurcating in 21% of the cases, with the presence of the diagonal artery. The anterior interventricular artery ended up at the apex in 79.7% of the cases, and the circumflex artery at the posterior aspect of the left ventricle in 64% of the case, this artery never reached the posterior interventricular sulcus. An anastomosis between the terminal branches of the anterior interventricular artery and the posterior interventricular artery was found in 7.6% of the specimens. The antero-superior branch of the anterior interventricular artery occurred in 89.9% of the hearts. A left marginal branch was observed in 87.9% of the cases with a diameter of 2.25±0.55 mm. Conclusion: Compared with humans, pigs have shorter left coronary artery trunks and branches; even the circumflex artery never reaches the posterior interventricular sulcus. Our findings are useful for the design of experimental hemodynamic and procedural models.